Fuzzy logic based obstacle avoidance strategy for mobile robot - Lee, Jeng Ye (2016)
The application of mobile robot often used in an inappropriate place for human. Sometime, it would involve in unknown environment. Obstacle avoidance are the key feature to control the mobile robot in order to avoid collision which provide safety to the mobile robot and the environment object. Obstacle avoidance is basically a strategy to define an obstacle by processing the distance between it, decision making in controller and giving output which control the movement or motion of the mobile robot. In this research, an obstacle avoidance strategy is using fuzzy logic approach to control the action of mobile robot was designed. The simulation design and algorithms of the obstacle avoidance with fuzzy inference system is described. The consideration of obstacle are depend on the data calculated throughout the design. The result shown are included on three model which is the target driven model, obstacle avoidance target driven model and multiple obstacle avoidance target driven model. The mobile robot are able to avoid all obstacle that set on the simulation environment.